The effects of color cues on typically developing preschoolers' speed of locating a target line drawing: implications for augmentative and alternative communication display design. - Thistle JJ; Wilkinson K (American Journal of Speech-Language Pathology, 2009)
PURPOSE: This research examined how the presence of color in relation to a target within an augmentative and alternative communication array influenced the speed with which typically developing preschoolers located a target line drawing. METHOD: Fifteen children over the age of 4 years (from 4;2 [years;months] to 5;4) and 15 children under the age of 4 years (2;10-3;11) participated. Participants were asked to find a target line drawing of foods (e.g., banana and tomato) among an array of 12. The reaction time of locating the target was measured across 4 conditions in which the foreground color and the background color of the line drawing were manipulated. RESULTS: For all participants, line drawings featuring foreground color provided greater advantages in the speed of locating the target compared with drawings featuring only background color. Younger participants demonstrated faster reaction times when color was limited to the foreground. CONCLUSION: Clinicians should consider incorporating color in the foreground of the line drawing when constructing visual displays. Targets that contain only background color but no foreground color appear to have a negative effect on the speed with which younger children can locate a target. Further research is needed to determine the effects in children with disabilities.